Anaplastic thyroid cancer. Is there a light at the end of the tunnel? - A. L. Pylev; A. A. Zhandarova; K. S. Petrov; D. S. Romanov; V. A. Lisovoy; S. V. Golub (Опухоли головы и шеи)
Anaplastic thyroid cancer is one of the most prognostically unfavorable tumors. This disadvantage traditionally consisted of a rapid increase in the size of the primary tumor with a tendency to the development of asphyxia and the rapid appearance of distant metastases, as well as a poor response to the recommended treatment methods. The result of many years of efforts by oncologists around the world were several treatment regimens, including an ideal amount of surgical intervention, chemotherapy and radiation therapy, but the effectiveness of this treatment, as well as the patient’s life expectancy after it, could not be called satisfactory. Improving the understanding of the molecular genetic characteristics of tumors, including anaplastic thyroid cancer, provided us with information on two possible features of the genetic apparatus of tumor cells that can have clinical significance: V600E mutations in the BRAF gene and fusion of NTRK genes. The clinical example described in this article is probably the first Russian illustration of the effectiveness of anti-BRAF therapy in a patient with anaplastic thyroid cancer. From our point of view, the benefit of this example is not only to demonstrate the effectiveness of modern targeted therapy, but also the need not to abandon other treatment methods, in this case, radiation therapy to the area of the primary tumor (and by analogy with this, surgical removal of the thyroid tumor glands in case of its resectability).